Combating Climate Change through water resource conserving technologies - Sudhishri, Susama; Dass, Anchal; Choudhury, P. R. (Indian Farming, 2015)
Resource management through integrated watershed management holds promise with integrate conservation and production technologies which ensure maximum in situ rainwater conservation, harvest rainwater for recycling to high value crops to support establishment of tree crops and recharging groundwater by integration of crop production and recycle and reuse of waste water, land use according to land capability possible through diversification. However people’s participation and training is required for effective adoption of the above described technologies for mitigation and adaptation to climate change.